Distribution of crown fracture in anterior teeth of the children with cerebral palsy - Sativa, Liariza; Hidayat, Syarief; Setiawan, Arlette Suzy Puspa Pertiwi (Universitas Padjadjaran, 2010)
Introduction: Crown fracture is a fracture involving enamel only or enamel and dentin with or without pulp exposure. Crown fracture in children may disrupt the speaking and masticating function, aesthetics, and permanent tooth eruption.The condition of the oral cavity of patients with cerebral palsy (CP) characterized by increased frequency of tooth fracture. Purpose of study is to examine distribution of crown fracture anterior teeth of children with cerebral palsy. Methods: Type of research was descriptive. Sample collected by Total Sampling. The sample numbers were 43 children with cerebral palsy. Data were obtained by clinical examination. WHO classification about crown fracture was used to evaluate oral and dental hygiene. Results: The result of this study showed that 39 children (90,7%) had crown fractures in anterior teeth. The 39 children consisted of 22 boys (51,17%), 17 girls (39,53%). Crown fracture in anterior teeth of the children with cerebral palsy is 60,47% in the upper jaw. Conclusion: The fracture of the anterior crown of the anterior teeth that are found is the fracture in the enamel. The anterior crown fracture is more common in boys and is found in maxillary anterior teeth of maxillary incisors.